128k views
13 votes
Simplify the expression: 6(x+y)+y−(x+3)

User Mwoelk
by
4.4k points

1 Answer

12 votes


\large\displaystyle\text{$\begin{gathered}\sf \bf{ 6(x+y)+y-(x+3)} \end{gathered}$}

Put the parentheses using: - (a + b)(= -a -b).


\large\displaystyle\text{$\begin{gathered}\sf \bf{-\left(x+3\right)=-x-3 } \end{gathered}$}


\large\displaystyle\text{$\begin{gathered}\sf \bf{=6\left(x+y\right)+y-x-3 } \end{gathered}$}

Expand 6(x+y): 6x+6y.


\large\displaystyle\text{$\begin{gathered}\sf \bf{=6x+6y+y-x-3 } \end{gathered}$}

Add like elements 6y+y=7y


\large\displaystyle\text{$\begin{gathered}\sf \bf{=6x+7y-x-3 } \end{gathered}$}

Group Like Terms


\large\displaystyle\text{$\begin{gathered}\sf \bf{=6x-x+7y-3 } \end{gathered}$}

Add like elements 6x-x=5x.


\large\displaystyle\text{$\begin{gathered}\sf \bf{\red{=5x+7y-3 \ \ \Rightarrow \ \ \ Answers }} \end{gathered}$}

User Baalrukh
by
4.4k points